2017
DOI: 10.4314/as.v15i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and preliminary evaluation of local germplasm of <i>Telfairia occidentalis</i> Hook F. accessions in Enugu, Nigeria

Abstract: The variability among 18 accessions of Telfairia occidentalis were studied by examining their yield and yield component traits. The 18 accessions were collected from four local government areas in Enugu State, Nigeria. The experiment was performed in a randomized complete block design replicated three times. Ih-M accession gave the highest fruit circumference and average fruit weight that was significantly higher than Ih-L accession. Ib-S accession gave the highest total fruit weight and number of fruits per h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…Table 2 showed the estimates of the variances and genetic parameters of the 10 maize genetic materials evaluated in 2015 and 2016 planting seasons for various quantitative traits. Variability of a trait is necessary for its inclusion in crop improvement programme (Chukwudi and Agbo, 2016;Ene et al, 2016). Percentage coefficient of variation (CV%) provides comparative assessment of the amount of variability between crop traits (Ene et al, 2016).…”
Section: Genetic Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 showed the estimates of the variances and genetic parameters of the 10 maize genetic materials evaluated in 2015 and 2016 planting seasons for various quantitative traits. Variability of a trait is necessary for its inclusion in crop improvement programme (Chukwudi and Agbo, 2016;Ene et al, 2016). Percentage coefficient of variation (CV%) provides comparative assessment of the amount of variability between crop traits (Ene et al, 2016).…”
Section: Genetic Variabilitymentioning
confidence: 99%
“…Principal component analysis is used in evaluating the patterns of variation in germplasm (Chukwudi and Agbo, 2016). The Principal component analysis results indicated that the first two axes explained 91.8% and 93.3% of the total variation in 2015 and 2016, respectively (Table 3).…”
Section: Principal Component Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Dry matter partitioning is influenced by the sink strength of an organ; its ability to compete for assimilates and the developmental stage of the plant (Chukwudi and Agbo 2016). Availability of assimilates, rate of assimilate remobilisation from source tissues, genotype and developmental stage of the plant also determine the dry matter partitioning in plants (Chukwudi and Agbo 2016;Smith et al 2018). Continuous cell division and expansion of carrot root during growth gives it an edge to accumulate available assimilates.…”
Section: Effects Of Environment Media and Variety On The Yield Compomentioning
confidence: 99%
“…In west Africa, the plant is a popular source of food, as well as medicinal, oil and fibre. In Western Africa, it is cultivated economically for its seed and young shoots (Orhuamen et al, 2012;Chukwudi and Agbo, 2017).…”
Section: Introductionmentioning
confidence: 99%